Hubungan Prokrastinasi Akademik dengan Perilaku Menyontek Siswa Kelas XI di Salah Satu Sekolah Kota Bogor - Amelia Fitriyani; Noneng Siti Rosidah; Reni Sinta Dewi (Program Studi Bimbingan Konseling Islam, Fakultas Tarbiyah Dan Ilmu Keguruan, Institut Ummul Quro Al-Islami Bogor, 2026)
Academic procrastination is a habit of delaying the completion of academic tasks that can have implications for the emergence of deviant behavior, such as cheating. This study aims to determine the relationship between academic procrastination and cheating behavior in grade XI students at a school in Bogor City. This study uses a descriptive method with a quantitative approach. This study was conducted on 182 respondents selected through a simple random sampling technique from a population of 333 students . In this study, the analysis technique used was the Product Moment correlation test. The data collection techniques used include observation, questionnaires and documentation. The results of the descriptive analysis show that most students who do academic procrastination are in the moderate category with a percentage of 93.4% and the level of cheating behavior is also in the moderate category with a percentage of 99.5%. The results of the correlation test show that there is a positive and significant relationship between academic procrastination and cheating behavior with a correlation coefficient value of 0.188 and a significance of 0.011 (p <0.05). These results indicate that the relationship between the two variables, namely academic procrastination and cheating behavior, is at a very low level of relationship. Based on these results, these findings identify that the higher the level of academic procrastination of students, the greater the tendency to cheat.